A review of paratuberculosis in dairy herds — Part 2: On-farm control. (April 2019) - McAloon, Conor G.; Roche, Steven; Ritter, Caroline; Barkema, Herman W.; Whyte, Paul; More, Simon J.; O'Grady, Luke; Green, Martin J.; Doherty, Michael L.
Highlights: Paratuberculosis, caused by Mycobacterium avium subspecies paratuberculosis (MAP), is associated with a number of production effects in cattle. There is some evidence that participation in a control program reduces the prevalence of the disease. There is little evidence in support of the impact of specific control measures on the incidence of MAP infection. Understanding farmer behaviour and motivating change on farm requires a tailored approach. Abstract: Bovine paratuberculosis is a chronic infectious disease of cattle, caused by Mycobacterium avium subspecies paratuberculosis (MAP). This is the second in a two-part review of the epidemiology and control of paratuberculosis in dairy herds. Several negative production effects associated with MAP infection have been described, but perhaps the most significant concern in relation to the importance of paratuberculosis as a disease of dairy cattle is the potential link with Crohn's disease in humans. Milk is considered a potential transmission route to humans and it is recognised that pasteurisation does not necessarily eliminate the bacterium. Therefore, control must also include reduction of the levels of MAP in bulk milk supplied from dairy farms. There is little field evidence in support of specific control measures, although several studies seem to show a decreased prevalence associated with the implementation of a combined management and test-and-cull programme. Improvements in vaccination efficacy and reduced tuberculosis (TB) test interference may increase uptake of vaccination as a control option. Farmer adoption of best practice recommendations at farm level for the control of endemic diseases can be challenging. Improved understanding of farmer behaviour and decision making will help in developing improved communication strategies which may be more efficacious in affecting behavioural change on farm.